2018
DOI: 10.1161/jaha.118.009910
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐Positive Status Is Associated With Poor Prognoses in Patients With Left Ventricular Noncompaction Cardiomyopathy

Abstract: Background Left ventricular noncompaction cardiomyopathy ( LVNC ) is a genetically and phenotypically heterogeneous disease. This study aims to investigate the genetic basis and genotype‐phenotype correlations in a cohort of Chinese patients with LVNC . Methods and Results A total of 72 cardiomyopathy‐associated genes were comprehensively screened in 83 adults and 17 children with LVNC by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
2
29
0
3
Order By: Relevance
“…Although there are an increasing number of reports describing genotype-phenotype correlations, genotype-phenotype correlations have been challenging. These reports of LVNC cohorts have been showing varying and often conflicting results [22][23][24][25][26][27]56]. A recent multicenter study analyzed 327 unrelated pediatric (n = 52) and adult (n = 275) patients with LVNC whose disease was categorized: (1) genetic (mutation positive), (2) probably genetic (mutation negative, family history positive), and (3) sporadic (mutation negative, family history negative) [22].…”
Section: Molecular Genetics and Phenotype-genotype Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are an increasing number of reports describing genotype-phenotype correlations, genotype-phenotype correlations have been challenging. These reports of LVNC cohorts have been showing varying and often conflicting results [22][23][24][25][26][27]56]. A recent multicenter study analyzed 327 unrelated pediatric (n = 52) and adult (n = 275) patients with LVNC whose disease was categorized: (1) genetic (mutation positive), (2) probably genetic (mutation negative, family history positive), and (3) sporadic (mutation negative, family history negative) [22].…”
Section: Molecular Genetics and Phenotype-genotype Correlationsmentioning
confidence: 99%
“…Li et al report their single-center genotype-phenotype correlations in Chinese patients with LVNC. A total of 72 cardiomyopathy-associated genes were comprehensively screened in 83 adults and 17 children with LVNC by targeted sequencing [24]. Overall, 42 pathogenic variants were identified in 38 patients (38%), with TTN, MYH7, MYBPC3, and DSP being the most commonly involved genes.…”
Section: Molecular Genetics and Phenotype-genotype Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort of 327 noncompaction cardiomyopathy including 52 children and 275 adults, the authors identified a higher prevalence of multiple hits in children (10%) than in adults (3%) ( p = .038) (van Waning et al, ). In another cohort of 100 patients, 6/83 adults were carriers of multiple variants (7%), and 1/17 children (5%) (Li et al, ). Further studies are necessary to clarify the prevalence of multiple hits in LVNC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrollment, genetic sequencing, variant classification, and follow‐up have been described in a previous study. (Li et al, ) Briefly, the diagnosis of LVNC was based on echocardiographic or cardiac magnetic resonance findings according to Jenni et al or Petersen et al criteria. (Jenni, Oechslin, Schneider, Attenhofer Jost, & Kaufmann, ; Petersen et al, ) Patients were eligible if they had LVNC and were willing to receive genetic testing and follow‐up.…”
Section: Methodsmentioning
confidence: 99%